A Song Remembered in Place: Tlingit Composer Mary Sheakley (Lxook) and Huna Tlingits in Glacier Bay National Park, Alaska. Issue Volume 39:Issues 3(2019) (September 2019) - Thornton, Thomas F.; Rudolph, Mary; Geiger, William; Starbard, Amy
Songs among the Tlingit of Alaska and Canada are important means for communicating and aligning relationships, knowledges, and emotions among humans, non-human persons, and ancestral lands. As potent expressions of individual and collective identity, heritage, and destiny, songs encapsulate ethnobiological, social, and geographic knowledges in a melodious, interspecific lingua franca . A particular ancestral or communal context, such as a potlatch or k u.éex', may call for a spiritual, mournful, or happy song to help effect a transition, for example from mourning to celebration or death to rebirth. Ceremonial songs are typically owned as property and performed by particular Tlingit matrilineal groups, known as clans, or their house groups. However, songs are in the first instance composed by individuals, typically in response to other unique events, such as extraordinary encounters with wildlife, disasters, or other remarkable circumstances. The composers of such songs, both men and women, are respected and honored for their skills. Mary Sheakley (Lx ook ) is one such figure. She composed the song presented here in response to a group of wolves that came to the beach and howled as she and her fellow paddler left their subsistence camp in what is now Glacier Bay National Park and Preserve around the turn of the twentieth century. In 1996, the song was spontaneously remembered by a contemporary elder and younger clan sister to Mary Sheakley, Amy Marvin, who, in turn, taught it to her younger clan daughter during a berry picking trip to Glacier Bay. Later, during that same trip, Amy Marvin deployed the song to cap an impromptu ritual of commemoration for Tlingit relatives that died in a tragic boating accident in the Park in the late twentieth century. The song was thus not only revived but elevated in status to become a "clan song, " which is now considered sacred property ( at.óow ) and performed during ceremonies, such as the potlatch or k u.éex' .